Easy Access to Bioorthogonal Click-to-Release Reagent Bishydroxy-trans-cyclooctene (C2TCO) and Harnessing of Its Rapid Labeling and Dissecting Feature in Multicycle Imaging - Arun, V.; Lee, Minju; Choi, Hongseo; Lee, Sangwoo; Choi, Junwon; Yoo, Tae Hyeon; Kim, Wook; Kim, Eunha (Bioconjugate Chemistry, 2025)
Bifunctional trans-cyclooctene (bTCO) with a carbamate or carbonate at the allylic position and tetrazine provide a promising bioorthogonal click chemistry pair for the click-to-release approach, successfully employed in various biotechnological applications. Herein, we demonstrate a simple and straightforward method to synthesize C2TCO, a symmetrical bTCO derivative with two hydroxyl groups at the allylic positions. The efficiently synthesized C2TCO at first was selectively functionalized with a fluorophore (C2TCO-FL), and the conjugate was labeled onto monoclonal antibodies (Ab-C2TCO-FL). The fluorophore of Ab-C2TCO-FL was easily removed from the antibody through the mild treatment of tetrazine, enabling multicycle fluorescent bioimaging. Next, an antibody-drug conjugate targeting PD-L1 was prepared using the linker based on C2TCO. The cytotoxic payload was efficiently released from the antibody upon tetrazine treatment, which induced cellular cytotoxicity.
Keywords: Allylics; Bi-functional; Biotechnological applications; Click chemistry; Cyclooctene; Labelings; Multi cycle; SIMPLE method; Straight-forward method; Tetrazines; Antibodies, Monoclonal; Cell Line, Tumor; Click Chemistry; Cyclooctanes; Fluorescent Dyes; Humans; Immunoconjugates; Optical Imaging